2014
DOI: 10.1002/col.21872
|View full text |Cite
|
Sign up to set email alerts
|

Refined CIECAM02 for bright surround conditions

Abstract: Displays such as mobile phones are viewed under surround conditions that vary from dark night to bright sunlight. The overall goal of this study is to test the appropriateness of CIECAM02 for mobile displays, and modify it according to any insufficiency found. Firstly, the testing of CIECAM02 is described using the visual data from 2‐inch display of three achromatic backgrounds (gray, black, and white), and three surround conditions (dark, dim, and average). Secondly, CIECAM02 was tested under four surround co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…It should be noted that our previous study 9 was carried out only under the dim surround condition, a condition likely for bedtime reading when all lights were off in the room. Little is known, however, whether the findings can apply to other viewing conditions, such as the average surround condition or even the bright condition 11 in which many people are using their mobile devices for reading, including web browsing. Several studies have shown that the illuminance level had a significant impact on visual performance.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that our previous study 9 was carried out only under the dim surround condition, a condition likely for bedtime reading when all lights were off in the room. Little is known, however, whether the findings can apply to other viewing conditions, such as the average surround condition or even the bright condition 11 in which many people are using their mobile devices for reading, including web browsing. Several studies have shown that the illuminance level had a significant impact on visual performance.…”
Section: Introductionmentioning
confidence: 99%
“…A correction has been made to the original CIECAM02 equation for the chromatic induction factor N cb . 1 In an earlier study 17,18 of the colour appearance of stimuli presented against a black background, the CIECAM02 model did not predict the colourfulness well. It is proposed to change the value of the power in the original chromatic induction factor, Eq.…”
Section: Correction Of the Chromatic Induction Factormentioning
confidence: 95%
“…[15][16][17] However, the CIECAM02 has been shown to be less useful for predicting the performance of mobile displays subjected to a wide variety of illumination conditions. 16,17 Also, even after refining the CIECAM02 model specifically for mobile displays the resulting color accuracy was shown to leave much room for improvement. 16,17 For this reason, we chose a different approach to account for ambient illuminance.…”
Section: Ambient Lighting and Adaptationmentioning
confidence: 99%